2015
DOI: 10.1080/00423114.2015.1034730
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on railway track geometry condition monitoring from in-service railway vehicles

Abstract: This paper presents a view of the current state of monitoring track geometry condition from in-service vehicles. It considers technology used to provide condition monitoring; some issues of processing and the determination of location; how things have evolved over the past decade; and what is being, or could/should be done in future research. Monitoring railway track geometry from an in-service vehicle is an attractive proposition that has become a reality in the past decade. However, this is only the beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
142
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(149 citation statements)
references
References 43 publications
1
142
0
6
Order By: Relevance
“…Typically a tachometer measures the rotation speed of a non-driven axle belonging to a wheel set usually in revolution/minute. British railway engineers, Weston et al (2015Weston et al ( :p.1064, have asserted that "The speed of rotation of an unpowered wheel and the odometer is the integration of the tachometer with respect to time multiplied by the wheel circumference to convert rotations per unit time into distance.". Distance measurement of a traveling vehicle is done in a direct way applying distance sensors.…”
Section: Measuring Devices Of Track Irregularitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically a tachometer measures the rotation speed of a non-driven axle belonging to a wheel set usually in revolution/minute. British railway engineers, Weston et al (2015Weston et al ( :p.1064, have asserted that "The speed of rotation of an unpowered wheel and the odometer is the integration of the tachometer with respect to time multiplied by the wheel circumference to convert rotations per unit time into distance.". Distance measurement of a traveling vehicle is done in a direct way applying distance sensors.…”
Section: Measuring Devices Of Track Irregularitiesmentioning
confidence: 99%
“…It should be noted that it is hard to measure the movements, say, only into the vertical direction, since the ends of the sensor will surely have certain lateral and longitudinal displacements as well. In this respect, Weston et al (2015Weston et al ( :p.1066 reported that "The capacitative or the inductive displacement sensors are more robust but can only measure small displacements. ".…”
Section: Measuring Devices Of Track Irregularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite past effort to understand the complex behaviour of railway tracks, enhance its performance [9][10][11][12] and develop tools to help in the asset management process [13][14][15][16] needed on the relationship between the characteristics of the train-track system and the development of track geometry defects [17]. Previous studies focused mostly on the influence of track geometry defects on the vehicle dynamics, in terms of ride comfort and derailment risk [3,14,[18][19][20][21][22], while others focused on the wheel-rail interface [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of railway track geometry from an 'in-service' vehicle has become an increasingly attractive proposition over the past decade (Weston et al, 2015). Track geometry measurement systems using in-service vehicles has been developed around the world but they are still in an early developmental phase.…”
mentioning
confidence: 99%